Mycochemical analysis and anticancer activity of endophytic Aspergillus nomius against MCF7 human breast cancer cell line - Rohit Shankar Mane; Ankala Basappa Vedamurthy (International Journal of Pharma and Bio Sciences, 2020)
The objective of the present research investigation was to purify potent drug molecule from endophytic Aspergillus nomius against MCF7 human breast cancer. The fungus crude extract from Aloe vera was obtained, dried, weighed and stored. The qualitative and quantitative mycochemical analyses of different solvent extracts were performed as per standard protocols. Further the potent extract was used for anticancer activity against MCF7 human breast cancer cell line by SRB method. The crude extract of different solvents showed the presence of alkaloids, terpenoids, steroids, tannins, saponins, flavonoids, phenols, coumarins, quinones and glycosides. The aqueous extract showed high phenolic content at the rate of 27.0090±0.04129 mg and flavonoids content at the rate of 63.47± 0.88059 mg as compared to other solvents. The Sulphorhodamine B assay showed 98.39±0.0250 and 40.81±0.0470 MCF7 cell line viability at 100 µg and at 500 µg with an IC50 value of 459.60 μg respectively. The fungus derived bioactive compounds showed effective cell cycle disruption and apoptosis. Present investigation is the first report of the fungus for their mycochemical analysis and prominent in vitro anticancer activity.